(untitled) (Forum for Linguistic Studies, 2024)
This research is motivated by various problems and negative views from the public regarding low performance accountability of the State Civil Apparatus, lack of discipline and weak morals such as work programs that are not completed, performance targets that are not achieved, dishonest behavior that is often involved in corruption, employees who are absent, arrive late. but going home early, as well as other events that do not comply with the rules. The aim of this research is to obtain information, description and analysis of learning management in basic training for prospective civil servants (CPNS) in order to increase the accountability of ASN performance. This research is qualitative research with a case study method. The data collection techniques used were observation, literature study, interviews and documentation. Data were analyzed using data reduction, data presentation, and drawing conclusions. Technique for checking data validity using triangulation of sources and techniques. The management theory from Terry (2005), the civil servant performance theory from Dharma (2016), and the learning theory from Qomar (2018). The results of this research show that the basic training planning (Latsar) was made by referring to the Regional Medium Term Development Plan (RPJMD), and the strategic plan and was planned according to submissions from the Regional Apparatus Organization (OPD) which were studied in the training needs analysis. The organization is regulated by a task division mechanism, based on a decision letter from the Head of the Agency relating to the organizational structure of the training management program which is generally understood and implemented by the Personnel and Human Resources Development Agency (BKPSDM). The tasks of the Organizational Structure are carried out according to the duties and functions of the Basic Training participants (Latsar) according to the formation of the participants in the Regional Apparatus Organization (OPD). The implementation of Latsar at BKPSDM is carried out in accordance with planning, apart from providing quality training for Latsar participants, the committee also pays great attention to the health of Latsar participants. Supervision of basic training is carried out daily by Class Observers during distance learning. Meanwhile, during classical times, supervision is carried out by the Pamong. Obstacles that occur include administrative, organizational and budgetary. Infrastructure and human resource (HR) problems where there are still limited Wisdyaiswara professional staff according to their fields and the obstacles to a lack of learning infrastructure, this can be overcome by increasing socialization and coordination in an active and integrated manner. Careful preparation is needed from the organizers, conveying information through outreach and letters and utilizing the class leader. The conclusion of this research is that the implementation of basic CPNS training in order to increase the accountability of ASN performance at the West Bandung Regency Human Resources Development Personnel Agency (BKPSDM) has been carried out based on a management approach.